MODEL SUPPLY CHAIN RESILIENCE USAHA KERAJINAN KARAWO MENGGUNAKAN METODE MACROERGONOMIC ANALYSIS AND DESIGN BERDASARKAN PERSPEKTIF RISK MANAGEMENT (STUDI KASUS UMKM XY, KABUPATEN GORONTALO) - Tjahjani, Ida Kusnawati; Hatta, Mochammad -; Mohammad, Silvana - (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2025)
Karawo as a typical Gorontalo embroidery craft has been widely known by the public. Sales of karawo handicrafts which continue to increase every year at the same time show the results of this karawo craft apart from being a traditional and tourism activity, it also supports economic development in the Gorontalo area. This is also shown by UMKM XY which continue to compete with other MSMEs in producing the best products. The Macroergonomic Analysis and Design (MEAD) method is an approach that aims to design a system based on risk assessment that disrupts the smooth supply chain process in UMKM XY. The risk management approach is completed based on the SCOR method to map risks, House of Risk phase 1 to assess risk priorities, House of Risk phase 2 to determine risk mitigation priorities. Risks with the highest priority are labor carelessness (A6) with the mitigation priority of making controlled rules (M1) and delays in the production process (A2) with the mitigation priority of making production scheduling (M4). The design of the Supply Chain Resilience system is then formed, so that the process can be controlled and the whole system is properly integrated.